PROFIL EKSTRAK DAUN TIN (Ficus carica) SEBAGAI LACTAGOGUE MENGGUNAKAN KROMATOGRAFI LAPIS TIPIS (Jurnal Kesehatan Siliwangi, 2022)
Tin (Ficus carica) is one of the plants mentioned in the holy book Al-Quran. Tin leaves are proven safe and have many biological activities. People simply consume fig leaves by boiling or brewing dried fig leaves. The aim of this study is comparing several leaf extract preparations obtained by several method using thin layer chromatography to see their phytochemical profile as a lactagogue. Tin leaf extract was obtained through several methods, namely steeping, boiling, maceration with 50% and 70% alcohol and infusion of fresh tin leaves with room temperature water and boiling water. After the tin leaf extract was obtained, it was then tested by thin layer chromatography to see the pattern of the active substance attracted to each extract with a combination of several solvents. The thin layer chromatography profile in general shows almost the same pattern of the active substance. 50% ethanol and 70% ethanol showed more patterns in the thin layer chromatography profile. It is necessary to carry out further studies related to phytochemical testing on tin leaves both qualitatively and quantitatively.